Targeting Trimethylamine N-Oxide: A New Therapeutic Strategy for Alleviating Atherosclerosis - Jing, Lele; Zhang, Honghong; Xiang, Qiannan; Shen, Liang; Guo, Xiaoxia; Zhai, Changlin; Hu, Huilin (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis (AS) is one of the most common cardiovascular diseases (CVDs), and there is currently no effective drug to reverse its pathogenesis. Trimethylamine N-oxide (TMAO) is a metabolite of the gut flora with the potential to act as a new risk factor for CVD. Many studies have shown that TMAO is involved in the occurrence and development of atherosclerotic diseases through various mechanisms; however, the targeted therapy for TMAO remains controversial. This article summarizes the vital progress made in relation to evaluations on TMAO and AS in recent years and highlights novel probable approaches for the prevention and treatment of AS.